Islamic Republic of Iran : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Iran's 2005 Article IV Consultation highlights Fourth Five-Year Development Plan (FFYDP) and the Twenty-Year Vision. The country's real GDP growth reached 5 1\2 percent a year on average, unemployment declined, and macroeconomic indicators improved significantly, supported by favorable oil market conditions. By increasing the openness of the economy and removing major obstacles to trade and investment, the reforms introduced in the period 2000/01-2002/03 contributed significantly to this strong performance. However, the economy remains heavily dependent on oil. Demographic dynamics will also put increasing pressure on the labor market in the coming years.